A Qualitative Exploration of the Experiences of People Living Alone and Receiving Community-Based Palliative Care - O'Connor, Moira (Mary Ann Liebert, Inc Publishers, 2014)
Background: It is projected that in Australia there will be between 28% and 48% of palliative care patients living alone by the year 2031. As such, it will become increasingly important to provide appropriate home-based care in order to support these patients to be cared for and die at home. Aim: This study explored the experiences of community-based palliative care cancer patients who live alone without a caregiver and what psychosocial issues they face. Methods: Face-to-face semistructured interviews were conducted with eight participants, and constant comparison was used for the analysis. Findings: Four main themes emerged: (1) loss of social networks; (2) maintaining independence; (3) balancing independence and the need for assistance; and (4) planning for the end of life. Discussion: Participants balanced independence with the need to accept help in order to maintain independence. Participants became more flexible about their preferred place of death. Conclusion: The practice implications for working with people close to death who are living alone are that supports and assistance may be needed to maintain social networks and also a sense of independence.